The world's money : how it works - Clarke, William M.; Pulay, George (London : Allen & Unwin, 1970)
This book has been written primarily for people who are interested in knowing about the world's monetary crisis, yet who do not have enough basic knowledge to follow all the financial comments in the press, on radio and on television. It is a guide to the way the international monetary system works today and how it might work in the future.
Includes bibliographical references and index.
usc 13/04/2018
Loans
Keywords: Foreign exchange